Developing a sustainable bioprocess for the cleaner production of xylooligosaccharides: An approach towards lignocellulosic waste management. (20th September 2021) - Kumar, Vishal; Bahuguna, Ashutosh; Ramalingam, Srinivasan; Kim, Myunghee
Abstract: Lignocellulosic agricultural waste has the potential to be converted into several value-added products such as biofuels, oligosaccharides, organic acids, and other chemicals. Among oligosaccharides, xylooligosaccharides (XOS) are the major prebiotic compounds that can be produced from lignocellulosic waste through biocatalysis using microbial enzymes. XOS are highly regarded in the food and pharmaceutical sectors for their extensive health-boosting properties. Owing to the high demand for XOS, a lot of research is underway to develop technologies and bioprocesses for their sustainable and clean production. Conventional methods used for the production of XOS, such as autohydrolysis and chemical hydrolysis, are less sustainable and non-eco-friendly processes. Moreover, the quality of final product obtained using conventional methods is compromised. Bioconversion of lignocellulosic biomass using enzymatic hydrolysis and microbial fermentation to produce XOS is a favorable alternative to overcome this problem. This review highlights various factors that influence the sustainability and eco-friendly nature of the XOS production bioprocess. Optimizing the process parameters using different statistical tools may pave the way towards economical production of XOS with minimal use of resources. Moreover, the present review discusses about the lignocellulosic biorefinery that is involved in the conversion of agricultural wastes to several value-added products, which makes the bioprocess more economically sustainable. Collectively, modern technologies, including protein engineering, cell surface engineering, and metagenomics, are useful for the efficient bioconversion of lignocellulosic biomass to value-added products. Highlights: Lignocellulosic waste have potentials to produce a number of value added products. XOS production effected by raw materials, pretreatment and xylanolytic hydrolysis. Process parameters optimization and bioreactors designs improve XOS production. Development of sustainable and cleaner production technology for XOS production. Lignocellulosic biorefinery for co-production of XOS and value added products.